(untitled) (International journal of artificial intelligence, 2025)
Paremiological units—including proverbs, sayings, aphorisms, maxims, and other culturally fixed expressions—represent a central component of linguistic heritage. They serve not only as tools of communication but also as repositories of collective memory and social norms. This article provides an expanded academic investigation of the structural, semantic, cultural, and cognitive dimensions of paremiological units. Drawing on classical and contemporary scholarship, the study examines how these units encode metaphorical models, shape worldviews, and maintain cultural continuity across generations. Findings show that paremiological units continue to serve as dynamic communicative devices in modern discourse, especially in intercultural communication, digital media, and educational contexts.